The discovery of two novel near-full-length HIV-1 recombinant forms in Hebei, China - Jia, Jianru; Shi, Haoxi; Chen, Sisi; Zhang, Zhen; Shi, Penghui; Fan, Weiguang (Journal of the Pakistan Medical Association, 2025)
In the recent years, homosexual contact has been the most common route of transmission of human immunodeficiency virus type 1 (HIV-1) in Hebei, China. In this study, we have identified two novel HIV-1 unique recombinant forms (URFs) that originated from CRF01_AE/C (BDL120) and subtype B/C (BDX016) among men who have sex with men (MSM) in Hebei. A phylogenetic tree and recombination analysis of the near-full-length genome sequences showed that BDL120 was a recombinant form originating from CRF01_AE and subtype C, whereas BDX016 consisted of subtypes B and C, containing eight and nine fragments of each, respectively. In BDL120, four C fragments were inserted into the CRF01_AE backbone, whereas in BDX016, four B fragments were inserted into the C backbone. The findings indicate that the frequent occurrence of HIV-1 recombination events has enriched HIV Databases, reflecting HIV-1 diversity in Hebei. Keywords: HIV-1; Unique recombination form; Men who have sex with men; Near-full-length genome; Hebei.